Perlindungan Hukum Terhadap Konsumen Dalam Pelaksanaan Layanan Gopaylater pada Aplikasi Gojek - Imelda Mardayanti (STIE Bina Karya, 2023)
This research is a descriptive qualitative research. The problem approach used in this study is empirical juridical. Empirical juridical is an approach that prioritizes legal/juridical rules combined with examining facts related to research. The nature of this research is descriptive. Where a study aims to provide an analytical description of the facts obtained with the applicable laws and regulations to obtain a comprehensive picture of the Gojek Paylater Paylater process. The results of this study are legal protection provided by Gojek, namely preventive and repressive protection measures. One form of legal protection is to make legal rules that can serve as protection or reference for the community, as in Law no. 8 of 1999 regulates Consumer Protection (hereinafter referred to as UUPK). The Consumer Protection Act is a law that regulates legal protection for consumers. However, this Law also emphasizes that business actors have the right to obtain legal protection from consumers with bad intentions.